Elevated Angiopoietin-1 Serum Levels in Patients with Alzheimer's Disease. (10th October 2012) - Schreitmüller, Brigitte; Leyhe, Thomas; Stransky, Elke; Köhler, Niklas; Laske, Christoph
Abstract : Background . Alzheimer's disease (AD) is the most common cause of dementia in the elderly. AD is characterized by the accumulation of amyloid plaques and neurofibrillary tangles and by massive neuronal loss in the brain. There is epidemiologic and pathologic evidence that AD is associated with vascular risk factors and vascular diseases, contributing to cerebral hypoperfusion with consecutive stimulation of angiogenesis and upregulation of proangiogenic factors such as Angiopoietin-1 (Ang-1). Methods . In the present study, we measured Ang-1 serum levels in 42 patients with AD, 20 patients with mild cognitive impairment (MCI), and in 40 healthy elderly controls by ELISA. Results . We found significantly increased Ang-1 serum levels in patients with AD compared to control subjects ( P = 0.003 ) . There was no significant difference between MCI patients and healthy controls ( P = 0.553 ) or between AD and MCI patients ( P = 0.054 ) . The degree of cognitive impairment as measured by the mini-mental status examination (MMSE) score was significantly correlated with the Ang-1 serum levels in all patients and healthy controls. Conclusions . We found significantly increased Ang-1 serum levels in AD patients. We could also show an association between Ang-1 serum levels and the cognitive status in all patients and healthy controls. Thus, serum Ang-1 could be a potential candidate for a biomarker panel for AD diagnosis.